UN census ‘households’ and local interpretations in Africa since Independence - (:unkn) unknown (My University, 2015)
Since the 1950s, the UN Statistical Division has encouraged nations to standardize the definitions used in data collection. A key concept in censuses and surveys is the household: This is the unit for which information is collected and analyzed, and is thus an important dimension of data that are the basis for many policies. We aim to understand the tensions between conformity with UN guidelines and national priorities. We analyze the documentation around the UN household definition over this period. Using detailed census and survey documentary data for several African countries, especially Burkina Faso, Senegal, Uganda, and Tanzania, we examine the disparities between national census definitions of “household” and the UN definition. Perspectives from interviews with key informants within national statistical offices demonstrate the variability in the importance accorded to the UN harmonization aims and the problems that arise when these standardized approaches interact with local norms and living arrangements.
Keywords: African Research